Antenatal depressive symptoms among pregnant women: Evidence from a Southern Brazilian population-based cohort study - Coll, Carolina de Vargas Nunes (J Affect Disord, 2017)
BACKGROUND: Antenatal depression (AD) is a major public health issue but evidence regarding its prevalence and associated factors in low and middle-income countries (LMICs) is limited. The aim of the study was to estimate the prevalence and identify risk factors for AD among Brazilian pregnant women. METHODS: All women living in the urban area of the city of Pelotas, Southern Brazil, with confirmed pregnancy and estimated delivery date in the year 2015, were invited to take part. Eligible pregnant women were recruited from health services. Symptoms of antenatal depression were assessed using the Edinburgh Postnatal Depression Scale (EPDS) by face-to-face interviews. A cutoff-point of 13 or more was used to define probable AD. RESULTS: EPDS scores were available for 4130 women. The prevalence of AD was 16% (95%CI 14·9–17·1). After adjustment for potential confounders, the factors most strongly associated with higher EPDS scores were a previous history of depression (PR 2·81; 95%CI 2·44-3·25), high parity (PR 1·72; 95%CI 1·38-2·15 - ≥2 children vs. 1 child) and maternal education (PR 5·47; 95%CI 4·22-7·09 - 0–4 vs. ≥12 years of formal education). LIMITATIONS: EPDS was administered through face-to-face interviews rather than questionnaires and some women may have felt uncomfortable reporting their symptoms leading to underreporting and consequently underestimation of the prevalence found. CONCLUSION: AD prevalence is substantially higher in Brazil than in high-income countries (HICs) but similar to other LMICs. Our study identified relevant risk factors that may be potential targets to plan interventions, particularly a history of depression.